Catholic Theological Union - Bevans, Stephen Bennett (Interreligious Studies and Intercultural Theology, 2019)
Robert J. Schreiter is one of today’s most important and influential theologians. This essay suggests that the key to Schreiter’s thought is his identity and spirituality as a Missionary of the Precious Blood. It is this identity and spirituality that moves him to do theology in the context of today’s globalized and polarized world, offering reflections on the possibility of reconciliation and peacemaking as effective ways of engaging in mission today. The theology that results from such reflections is grounded not only in theological method, but also in the content and method of social philosophy and the social sciences.